2004
DOI: 10.1111/j.1365-2036.2004.02066.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the motilin agonist KC 11458 on gastric emptying in diabetic gastroparesis

Abstract: SUMMARYBackground: KC 11458, a motilin agonist without antibiotic properties, accelerates gastric emptying in animals and healthy humans. Aim: To evaluate the acute effects of KC 11458 on gastric emptying in diabetic gastroparesis. Methods: Twenty-nine patients (6 type 1 and 23 type 2) with gastroparesis underwent assessments of: (i) gastric emptying of a solid/liquid meal using scintigraphy, (ii) glycaemic control (blood glucose at 0, 30, 60, 90 and 120 min during the gastric emptying measurement) and (iii) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 31 publications
1
21
0
2
Order By: Relevance
“…Several studies have in different ways found an association between gastric emptying and the postprandial glucose. 9,11,20,21,23,[35][36][37][38][39][40] In our study we found that the plasma glucose response was blunted in DGP, with a mean peak glucose level that was approximately 1 mmol/L less in DGP, even though there were no differences in the plasma glucose level before the meal between the DGP and DNGP. Contrary to our findings, Punkkinen et al found no significant differences in the postprandial glucose between DGP and DNGP; however in that study, there was a tendency toward group differences in the fasting glucose levels, which may have influenced the meal response.…”
Section: Discussionmentioning
confidence: 58%
“…Several studies have in different ways found an association between gastric emptying and the postprandial glucose. 9,11,20,21,23,[35][36][37][38][39][40] In our study we found that the plasma glucose response was blunted in DGP, with a mean peak glucose level that was approximately 1 mmol/L less in DGP, even though there were no differences in the plasma glucose level before the meal between the DGP and DNGP. Contrary to our findings, Punkkinen et al found no significant differences in the postprandial glucose between DGP and DNGP; however in that study, there was a tendency toward group differences in the fasting glucose levels, which may have influenced the meal response.…”
Section: Discussionmentioning
confidence: 58%
“…The effect of KC 11458, a motilin agonist without antibiotic properties, on gastric emptying was studied in 29 patients with diabetic gastroparesis. KC 11458 in a dose of 8 mg three times daily failed to enhance gastric emptying and tended to worsen postprandial symptoms [53]. These data suggest that the therapeutic potential of macrolide-type prokinetic drugs is probably limited.…”
Section: Pharmacologic and Electric Effectsmentioning
confidence: 90%
“…A recent study evaluated the effect of one motilide, KC11458, on gastric emptying in diabetic gastroparesis [44 • ]. Unfortunately, the drug had no significant effect on gastric retention of either solids or liquids and actually slightly worsened the upper gastrointestinal symptoms in these patients [44]. Repair of gastroschisis (a congenital fissure of the abdominal wall usually involving protrusion of the small and part of the large intestine) in infants is frequently prolonged, and these patients are susceptible to the complications associated with parenteral nutrition.…”
Section: Motilinmentioning
confidence: 97%